Kontrola ogólna i kontrola aplikacji w systemie informatycznym rachunkowości - Szymczyk-Madej, Katarzyna (General Control and Application Control in an Accounting Information Systems, 2006)
Development of information technology (IT) and data storing devices as well as availability of Accounting Information Systems (AISs) on the Polish market have led not only to common utilization of IT in the field of book-keeping, but also to substantial changes in keeping and storing books. Variety of software packages, which are developed by applying the latest IT achievements, causes that AISs, which are utilized by business entities, function based upon various solutions. Accounting Information Systems, however, have to fulfill many requirements. The basic of them are security and quality of data. Therefore, nowadays both general and application controls are introduced to AISs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 405-414